2004
DOI: 10.1038/sj.gene.6364097
|View full text |Cite
|
Sign up to set email alerts
|

Death receptor 3 (DR3) gene duplication in a chromosome region 1p36.3: gene duplication is more prevalent in rheumatoid arthritis

Abstract: The death receptor 3 (DR3) gene is a member of the apoptosis-inducing Fas gene family. In the current study, fluorescence in situ hybridization (FISH) and Fiber-FISH revealed the existence of a second DR3 gene B200 kb upstream of the original DR3 gene. The existence of the duplicated DR3 gene was confirmed by sequencing the corresponding human artificial chromosome clones as well as with quantitative PCR that measured the ratio of the DR3 gene mutation (Rm), intrinsic to rheumatoid arthritis (RA) patients, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 18 publications
0
26
0
1
Order By: Relevance
“…Shortly thereafter, TL1A-induced IFNγ expression was also reported in preparations of mononuclear cells isolated from the lamina propria, the magnitude of which was mildly increased in patients with active Crohn's disease [4]. In the first of a continuing series of contributions to this field, Stephan Targan's group next demonstrated that in the absence of TCR signals, TL1A leads to a dose-and IL-12/IL-18-dependent increase in IFNγ production by CD4+, CD8+, NK, and NKT cells [23]. These studies were then further defined when it was demonstrated that although either TCR signaling or IL-12/IL-18 are required for TL1A to enhance IFNγ production by T cells, IL-12/IL-18 are not required in addition to TCR signaling for TL1A to enhance IFNγ production [27].…”
Section: Tl1a:tnfr25 In T Cell Functionmentioning
confidence: 93%
See 1 more Smart Citation
“…Shortly thereafter, TL1A-induced IFNγ expression was also reported in preparations of mononuclear cells isolated from the lamina propria, the magnitude of which was mildly increased in patients with active Crohn's disease [4]. In the first of a continuing series of contributions to this field, Stephan Targan's group next demonstrated that in the absence of TCR signals, TL1A leads to a dose-and IL-12/IL-18-dependent increase in IFNγ production by CD4+, CD8+, NK, and NKT cells [23]. These studies were then further defined when it was demonstrated that although either TCR signaling or IL-12/IL-18 are required for TL1A to enhance IFNγ production by T cells, IL-12/IL-18 are not required in addition to TCR signaling for TL1A to enhance IFNγ production [27].…”
Section: Tl1a:tnfr25 In T Cell Functionmentioning
confidence: 93%
“…These early functional data were complemented by human genetic studies implicating TNFR25:TL1A in autoimmune disease, particularly rheumatoid arthritis, inflammatory bowel disease, and type 1 diabetes [6,13,22,23,32,41]. Because each of these diseases are variably characterized by a combination of type-1 inflammation, dependence upon immune complex formation or reactivity to antigens which should normally not cross the threshold for TCR activation, there was urgent need to begin examining the function of TL1A:TNFR25 in disease model systems in vivo.…”
Section: Tl1a:tnfr25 In Auto-aggressive Diseasementioning
confidence: 96%
“…In this regard, it is noteworthy that DR3 gene duplication in chromosome region 1p36.3 is prevalent in RA patients (35), raising the possibility that TL1A and DR3 interaction indeed plays a role in human RA pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…TL1A was originally reported to be expressed exclusively in endothelial cells (Migone et al, 2002), but more recently TL1A has been found to be highly expressed in dendritic cells (DCs) after in vitro activation and in Crohn's disease, rheumatoid arthritis, and mouse models of inflammatory bowel disease, (Bamias et al, 2003;Bamias et al, 2006;Cassatella et al, 2007). Genetic variants in TL1A and DR3 have also been associated with Crohn's disease and rheumatoid arthritis, respectively (Osawa et al, 2004;Yamazaki et al, 2005).…”
Section: Introductionmentioning
confidence: 97%